2020
DOI: 10.1111/asj.13441
|View full text |Cite
|
Sign up to set email alerts
|

Examination of milk microbiota, fecal microbiota, and blood metabolites of Jersey cows in cool and hot seasons

Abstract: Milk is an ideal environment for the growth of many microorganisms due to its high nutritional content. A lot of species, including both desirable and undesirable ones, are detected in raw milk, and thus the milk microbiota may affect the quality and safety of dairy products (Quigley et al., 2013). Some bacteria in milk, including members of Lactococcus spp., Lactobacillus spp., Streptococcus spp., Propionibacterium spp., and Leuconostoc spp. can exert a beneficial role in altering the taste, appearance, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…In our study, bedding treatments did affect the relative abundance of the prevalent bacteria, e.g., Firmicutes , Bacteroidetes , Proteobacteria and Actinobacteria . The proportion of dominant bacteria was similar to the report that Proteobacteria and Firmicutes were two prevalent phyla by Nguyen et al [ 44 ]. Ganda et al [ 45 ] reported that the milk microbiota from healthy cows were also dominated by Proteobacteria and Firmicutes .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, bedding treatments did affect the relative abundance of the prevalent bacteria, e.g., Firmicutes , Bacteroidetes , Proteobacteria and Actinobacteria . The proportion of dominant bacteria was similar to the report that Proteobacteria and Firmicutes were two prevalent phyla by Nguyen et al [ 44 ]. Ganda et al [ 45 ] reported that the milk microbiota from healthy cows were also dominated by Proteobacteria and Firmicutes .…”
Section: Discussionsupporting
confidence: 89%
“…It has been demonstrated that the milk microbiota is a dynamic community with the shift of environment [ 11 , 40 , 41 , 43 ]. Nguyen et al [ 44 ], found that differences in milk microbiota derived from two farms at the family level. In our study, bedding treatments did affect the relative abundance of the prevalent bacteria, e.g., Firmicutes , Bacteroidetes , Proteobacteria and Actinobacteria .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of seasonal changes in the gut microbiome, Nguyen et al found that the dominant families of the fecal microbiota ( Ruminococcaceae, Bacteroidaceae , etc.) were not affected by seasons, while the content of Staphylococcaceae and Methylobacteriaceae were different in the summer and winter [ 20 ]. Furthermore, since the feed provided to the rumen and hindgut may differ, the microbiome in the rumen and feces are likely also different [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The microbiota in raw cow milk has been shown to vary by geographic region and season (Kim et al, 2017;Nguyen et al, 2020). For instance, the families Methylobacteriaceae and Moraxellaceae are prevalent in raw cow milk of cool season, whereas the families Staphylococcaceae, Bacillaceae, Ruminococcaceae, and Veillonellaceae are abundant in hot season (Nguyen et al, 2020). The abundance of the genera Corynebacterium, Pediococcus, Macrococcus, and Acinetobacter in the raw milk vary in different geographical locations (Kim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%